Longitudinal Analysis of Music Education on Executive Functions in Primary School Children - Jaschke, Artur C.; Honing, Henkjan; Scherder, Erik J. A. (Frontiers in Neuroscience, 2018)
Background: Research on the effects of music education on cognitive abilities has generated increasing interest across the scientific community. Nonetheless, longitudinal studies investigating the effects of structured music education on cognitive sub-functions are still rare. Prime candidates for investigating a relationship between academic achievement and music education appear to be executive functions such as planning, working memory and inhibition. Method: 147 primary school children, Mage= 6.4 years, SD=.65 were followed for 2.5 years. Participants were randomised into four groups: two music intervention groups, one active visual arts group and a no arts control group. Neuropsychological tests assessed verbal intelligence and executive functions. Additionally, a national pupil monitor provided data on academic performance. Results: Children in the visual arts group perform better on visuospatial memory tasks as compared to the three other conditions. However, the test scores on inhibition, planning and verbal intelligence increased significantly in the two music groups over time as compared to the visual art and no arts controls. Mediation analysis with executive functions and verbal IQ as mediator for academic performance have shown a possible far transfer effect from executive sub-function to academic performance scores. Discussion: The present results indicate a positive influence of long-term music education on cognitive abilities such as inhibition and planning. Of note, following a two-and-a-half year long visual arts program significantly improves scores on a visuospatial memory task. All results combined, this study supports a far transfer effect from music education to academic achievement mediated by executive sub-functions.